SCN9A variant in a family of mixed breed dogs with congenital insensitivity to pain. (11th January 2023) - Gutierrez‐Quintana, Rodrigo; Christen, Matthias; Faller, Kiterie M. E.; Guevar, Julien; Jagannathan, Vidhya; Leeb, Tosso
Abstract: Background: Congenital insensitivity to pain (CIP) and hereditary sensory and autonomic neuropathies (HSANs) are a rare group of genetic disorders causing inability to feel pain. Three different associated variants have been identified in dogs: 1 in Border Collies, 1 in mixed breed dogs, and 1 in Spaniels and Pointers. Objectives: To clinically and genetically characterize CIP in a family of mixed breed dogs. Animals: Two mixed breed dogs from the same litter were independently presented: 1 for evaluation of painless fractures, and the other for chronic thermal skin injuries. Methods: Physical, neurological, and histopathological evaluations were performed. Whole genome sequencing of 1 affected dog was used to identify homozygous protein‐changing variants that were not present in 926 control genomes from diverse dog breeds. Results: Physical and neurological examinations showed the absence of superficial and deep pain perception in the entire body. Histopathological evaluations of the brain, spinal cord and sensory ganglia were normal. Whole genome sequencing identified a homozygous missense variant in SCN9A, XM_038584713.1:c.2761C>T or XP_038440641.1:(p.Arg921Cys). Both affected dogs were homozygous for the mutant allele, which was not detected in 926 dogs of different breeds. Conclusions and Clinical Importance: We confirmed the diagnosis of CIP in a family of mixed breed dogs and identified a likely pathogenic variant in the SCN9A gene. The clinical signs observed in these dogs mimic those reported in humans with pathogenic SCN9A variants causing CIP. This report is the first of a spontaneous pathogenic SCN9A variant in domestic animals.